(untitled) (Stavební obzor - Civil Engineering Journal, 2022)
The problem of the “best” choice in terms of the ecological, durable, cheap and energy-effective material of envelope construction has been considered in the paper. For the numerical assessment of the thermal performance, the MCDA techniques as Analytical Hierarchy Process (AHP) and Criteria Importance Theory (CIT) were used. There were proposed eight types of wall assemblies from a natural material, namely: Hempcrete, Adobe, Strawbale panel, Earthbag, Cordwood, SIP (plywood+ecofiber), Hempcrete+straw and Compositional building thermo-block. As a objective function for the search of the best alternative the integral index was proposed which consist of thermo-physical and economic criteria. As the thermo-physical criteria component of the index were taken the u-value of the envelope W/m2K, the dimensionless decrement factor of the envelope f and the internal areal heat capacity of the envelope k1, kJ/m2K according to ISO 13786:2017. As economic criteria of the integral index, the authors proposed the cost of the wall material Q, UAH/m2 and the mass of the wall m, kg/m2. The analysis of the conducted research has shown, that from the one hand there is no absolute “leader” in the ranking of the wall assemblies according to the proposed criteria and MCDA technique, but from the other hand by comparison of the results, there were revealed that the top three alternatives in both AHP and CIT technique are walls of “B”, “D” and “E” type with different point order, achieved in each MCDA calculation technique.